Ozdoby stroju wykonane z paciorków w kulturze wielbarskiej - Żyto, Kinga (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
The main purpose of the article is to present various forms of costume decoration in Wielbark culture. The analysis was based on well-known burials with an intact arrangement of monuments in the burial cavern. On this basis, decorations made of beads were highlighted. In addition to the necklaces that adorned the area of the neck and chest, vertical compositions are particularly noteworthy, in which the beads were discovered in a line from the level of the neck to the waist level. In addition, beads were used to trim robes in the form of applications. Another type are beads decorating belt and sachets or purses.